Evaluation of phenolic profile, antioxidant and anticholinesterase effects of Fuscoporia torulosa - Mehmet Emin Emin Duru; Gülsen Tel-Çayan; Ebru Deveci (International Journal of Secondary Metabolite)
In this study, we investigated antioxidant and anticholinesterase activities of the hexane, chloroform, acetone, methanol and water extracts of F. torulosa mushroom with total phenolic contents. Also, HPLC-DAD was used to identify phenolic profile of F. torulosa. The acetone and methanol extracts of F. torulosa with the highest total phenolic contents showed the highest antioxidant activity in all assays except metal chelating assay. Furthermore, antioxidant activities of the acetone and methanol extract were found to be higher than α-tocopherol and BHA used as standards in DPPH•, ABTS•+ and CUPRAC assays. When F. torulosa hexane extract (41.34±1.50 %) showed moderate AChE inhibitory activity, the acetone (40.78±0.30 %) and methanol (45.39±0.65 %) extracts of F. torulosa indicated moderate BChE inhibitory activity. Major phenolic compounds were identified as trans-2-hydroxy cinnamic acid (10.05 µg/g), gallic acid (5.01 µg/g) and p-coumaric acid (3.04 µg/g). These results suggest that F. torulosa mushroom could be used as a valuable natural antioxidant source for pharmaceutical industry.